Intérêt du préélevage de l'huître Crassostrea gigas en claire - Zanette, Yvan; Deslous-paoli, Jean-marc (ISTPM, 1983)
Since the disappearance of Crassostrea angulata LMK during the epizootics of 1970-72, Crassostrea gigas Thunberg has been cultivated in the Marennes-Oléron basin. The latter, which could reach its commercial size at 18 months (His, 1978), no longer reaches it until 36 months. The harvesting of these oysters as well as their pre-fattening is currently done mainly in the estuaries of the Charente and the Seudre. The growth of C. gigas could be improved by separating the oysters from collectors sooner than usually done and fattening them sooner. Depuis la disparition de Crassostrea angulata Lmk, lors des épizooties de 1970 -72, Crassostrea gigas Thunberg est cultivée dans le bassin de Marennes-Oléron. Cette dernière qui pouvait atteindre sa taille marchande dès 18 mois (His, 1978), ne l'atteint plus actuellement qu'en 36 mois. La collecte de ces huîtres ainsi que leur prégrossissement se font actuellement principalement dans les estuaires de la Charente et de la Seudre. Un détroquage précoce et un prégrossissement en claire permettraient d'améliorer la croissance de C. gigas.